Juridical Analysis Of Prosecution Application Against Traffic Violators Through E-Ticketed System With CCTV Footage As Evidence - Teguh Tri Prasetya; Eko Soponyono (Jurnal Daulat Hukum, 2019)
This study aims to identify and analyze the application of the prosecution and the inhibiting factors, as well as the implementation of action should be, against traffic violators through E-Traffic ticket system with CCTV footage as evidence. The approach method in this research is empirical juridical approach. Specifications are descriptive analytical research and analysis used is qualitative analysis. The results of this research are: 1) Implementation of action against traffic violators through E-Traffic ticket system with CCTV footage as evidence that E-Traffic ticket enacted to curb the traffic. If the conventional ticketed offenders will be dismissed by the officer and given a ticket, but the E-Traffic ticket there is not like it and if the offender has committed an offense. 2) inhibiting factors in the implementation of action against traffic violators through E-Traffic ticket system with CCTV footage as evidence, namely Traffic Police not yet have its own camera so that in its application to the camera's still a part of the Transportation Agency of Semarang. Data Regident must use a server connected to Traffic Police Coordinator and in every action must be coordinated to the Central Java Traffic Police Directorate which has the network. Supported yet the budget for delivery via Postal address listed on the vehicle registration is not yet fully in accordance with the ownership. 3) Implementation of action that should be against the violators of traffic through the E-Traffic ticket system with CCTV footage as evidence that by applying the principle of vicarious liability where a criminal liability imposed on a person for the actions of others (the legal responsibility of one person for the wrongful acts of another). This means that the current application and E-Traffic ticket system become Electronic Traffic Law Enforcement (ETLE) in can not be charged to the owner of the vehicle of origin, even though the vehicle has not been did name change / but still subject to the deed of sale and purchase of own popularity. That is because owners of vehicles, both cars and motorcycles, not entirely make the process behind the name. Keywords: Repression; Traffic Offenders; E-Traffic Ticket; CCTV Footage; Evidence.